SOSIALISASI DAN PENGUATAN PASTORAL TAHUN PARIWISATA HOLISTIK DI PAROKI SANTU MIKAEL KUMBA - Fransiska Widyawati (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
The Catholic Church of Ruteng Diocese has declared 2020 as the Pastoral Year of Holistic Tourism. The Church wants tourism to be an opportunity for Catholics to build the common good, and promote global brotherhood and unity. This Tourism Pastoral should be implemented in parishes, sub-parish, regions, and members of the Basic Ecclesiastical Communities (BEC) throughout the diocese. To introduce and implement tourism pastoral programs to the whole people, a Community Service Program (CSP) was designed. The CSP subject and partner were the BECs leaders in the Bethany Community of Santu Mikael Kumba Parish. The goal was for partners to recognize the nature of the 2022 Holistic Tourism Pastoral Year, recognize strategic programs and be willing to implement programs within their respective communities and BECs. The CSP method used consists of 3 main stages: preparation, implementation, and evaluation. As a result, the CSP socialization has been completed. The target partners were enlightened by the socialization and understood the work program of the Catholic Church better. They were also ready to implement existing programs and develop regional internal programs and KBGs. This program was recommended to be carried out more often, both in the same theme and in different contexts and themes.